Tracing Metal Dart Impacts Through 3D Reverse Modeling on the Northern Walls of Pompeii - Adriana Rossi; Silvia Bertacchi (Engineering Proceedings, 2025)
This study examines the first systematic documentation of a series of small impact marks on the northern walls of Pompeii, interpreted as the result of Roman metal dart projectiles launched during the Sullan siege in 89 BC. Using high-resolution, reality-based 3D models, comparative analysis, and reverse modeling techniques, the research explores the hypothesis that a distinctive fan-shaped configuration of quadrangular indentations may have been produced by a repeating catapult, known as the polybolos. The integration of close-range photogrammetry, laser scanning, and digital reconstruction tools demonstrates how virtual casts and comparative modeling can contribute to archaeological interpretations of ancient projectile weaponry.